Relationship Between ABCF2 Expression and Response to Chemotherapy or Prognosis in Clear Cell Adenocarcinoma of the Ovary. Issue 5 (1st June 2010) - Tsuda, Hiroshi; Ito, Kiyoshi; Yaegashi, Nobuo; Hirasawa, Akira; Sudo, Tamotsu; Kita, Tsunekazu; Terai, Yoshito; Kigawa, Junzo; Sugiyama, Toru; Aoki, Daisuke
Abstract : Objectives: The purpose of this study was to evaluate the association of ABCF2 (adenosine triphosphate-binding cassette superfamily F2) protein expression with response to chemotherapy and prognosis in patients with clear cell adenocarcinoma (CCC) of the ovary. Methods: One hundred sixty-five patients with CCC were studied, and cytoplasmic ABCF2 expression was detected by immunohistochemical staining. All patients underwent platinum-based primary chemotherapy followed by primary surgery. Results: Adenosine triphosphate-binding cassette superfamily F2 expression was detected in 118 (71.5%) of 165 patients and was not related to age or clinical stage. The response rate to chemotherapy in 38 patients with measurable disease was 47.3% (18/38). The response rate tended to be higher in patients without ABCF2 expression than in those with ABCF2 expression; however, this difference was not significant (66.7% vs 34.8%, P = 0.096). There was no significant difference in overall survival between ABCF2-positive and ABCF2-negative cases (median survival time, 1175 vs 1257 days; P = 0.24). Conclusions: Adenosine triphosphate-binding cassette superfamily F2 protein was highly expressed in CCC of the ovary, but expression was not related to age, clinical stage, chemoresponse, or prognosis.